Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 138848 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Tyrannus vociferans Swainson, 1826", "TaxonKey is Animalia" ] }, "Country is Mexico", "HasGeospatialIssue is true" ] } The dataset includes 138848 records from 221 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003936-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences